2017
DOI: 10.1371/journal.pone.0182292
|View full text |Cite
|
Sign up to set email alerts
|

Population structure and molecular genetic characterization of clinical Candida tropicalis isolates from a tertiary-care hospital in Kuwait reveal infections with unique strains

Abstract: Candida tropicalis is a frequently isolated yeast species causing bloodstream, urinary tract and other infections particularly in patients admitted to intensive care units (ICUs) and those requiring prolonged urinary catheterization (UC) or receiving broad-spectrum antibiotics (BSA). This study investigated clinical characteristics and genetic relatedness among C. tropicalis strains isolated from patients at Al-Amiri Hospital in Kuwait. C. tropicalis strains (n = 63) isolated from blood, genito-urinary, respir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
22
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 60 publications
5
22
0
1
Order By: Relevance
“…In fact all new Italian genotypes (DSTs 747-51 and 759) were not present in the C. tropicalis MLST database before and the unique deposited blood isolate with DST333 (the second most common genotype of this study) was previously reported from a Chinese patient hospitalized in a neurosurgery unit ( Fan et al, 2014 ). However, a recent global analysis of the MLST genotypes confirmed a lack of association between different genotypes and antifungal resistance, specimen type, or geographical locations ( Al-Obaid et al, 2017 ; Wu et al, 2017 ) even if the existence of an exclusive MLST clonal cluster from Italy suggests the occurrence of independent geographical evolution. Nevertheless, although the number of the isolates included in this study make up ∼20% (28/143) of the European C. tropicalis deposited in the MLST database, the amount of the examined Italian isolates was still too small to draw any solid conclusion and therefore further studies will be needed in order to corroborate our observations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact all new Italian genotypes (DSTs 747-51 and 759) were not present in the C. tropicalis MLST database before and the unique deposited blood isolate with DST333 (the second most common genotype of this study) was previously reported from a Chinese patient hospitalized in a neurosurgery unit ( Fan et al, 2014 ). However, a recent global analysis of the MLST genotypes confirmed a lack of association between different genotypes and antifungal resistance, specimen type, or geographical locations ( Al-Obaid et al, 2017 ; Wu et al, 2017 ) even if the existence of an exclusive MLST clonal cluster from Italy suggests the occurrence of independent geographical evolution. Nevertheless, although the number of the isolates included in this study make up ∼20% (28/143) of the European C. tropicalis deposited in the MLST database, the amount of the examined Italian isolates was still too small to draw any solid conclusion and therefore further studies will be needed in order to corroborate our observations.…”
Section: Discussionmentioning
confidence: 99%
“…Candida tropicalis is a diploid yeast that together with C. albicans, C. parapsilosis , and other less relevant Candida pathogens forms part of the so-called Candida CTG clade in which the CUG codon is translated as serine rather than leucine ( Papon et al, 2013 ). Genetically, the population structure of this fungus appears to be quite heterogeneous, and more complex ( Wu et al, 2012 ; Al-Obaid et al, 2017 ; Wu et al, 2017 ) than the one previously described by Tavanti et al (2005) using multilocus sequence typing (MLST) technique. However, compared to the C. albicans MLST database 2 , which contains genetic data from over 4000 isolates, the number of C. tropicalis isolates genotyped so far is still too small to provide a good estimate of the pattern of the genetic variation occurring in this species.…”
Section: Introductionmentioning
confidence: 88%
“…Both isolates (Kw3707/16 and Kw107/17) were initially identified by growth on CHROMagar Candida and Vitek 2 yeast identification systems. Identification was confirmed by Vitek MS, species-specific amplification, and PCR sequencing of the internally transcribed spacer (ITS) region of ribosomal DNA (rDNA), performed as described previously (15). Antifungal drug susceptibility testing (AST) was performed, and MICs were determined by Etest as described previously (16).…”
mentioning
confidence: 99%
“…The hot spot 1 (HS-1) and HS-2 regions of the FKS1 gene were amplified by using FKS1-1F (5=-GGTTTAGATATGTGGATGTCCTA-3=) plus FKS1-1R (5=-AAATGTTTCTCCATGG AGTCAAG-3=) and FKS1-2F (5=-CTACCAAGATTGGTGCTG-3=) plus FKS1-2R (5=-TATCTAG CACCACCAACAG-3=) primers, respectively, and PCR thermal and cycling conditions as described previously (15,25). Both strands of HS-1 and HS-2 amplicons were sequenced by using internal FKS1-1FS (5=-TTAGATATGTGGATGTCCTACTT-3=) or FKS1-1RS (5=-GTTTCTCCA TGGAGTCAAGATG-3=) and FKS1-2FS (5=-ACCAAGATTGGTGCTGGTA-3=) or FKS1-2R (5=-CTA GCACCACCAACAGTCA-3=) primers, respectively, and other sequencing reaction conditions as described previously (15,25). DNA sequence data were compared to the reference sequence from C. tropicalis (GenBank accession no.…”
mentioning
confidence: 99%
See 1 more Smart Citation